2022
DOI: 10.1080/10717544.2021.2023702
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nanocapsules blended polymeric hydrogel loaded with bupivacaine drug delivery system for local anesthetics and pain management

Abstract: Local anesthetics are used clinically for the control of postoperative pain management. This study aimed to develop chitosan (CS) with genipin (GP) hydrogels as the hydrophilic lipid shell loaded poly(ε-caprolactone) (PC) nanocapsules as the hydrophobic polymeric core composites (CS-GP/PC) to deliver bupivacaine (BPV) for the prolongation of anesthesia and pain relief. The swelling ratio, in vitro degradation, and rheological properties enhancement of CS-GP/PC polymeric hydrogel. The inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…The results ties well with Altuncu et al’s previous studies . It should be noted that the degradation ratios of FFK/PEGDA hydrogels have consistent trends, suggesting that the FFK/PEGDA hydrogels have the potential for long-term implantation …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results ties well with Altuncu et al’s previous studies . It should be noted that the degradation ratios of FFK/PEGDA hydrogels have consistent trends, suggesting that the FFK/PEGDA hydrogels have the potential for long-term implantation …”
Section: Resultsmentioning
confidence: 99%
“…30 It should be noted that the degradation ratios of FFK/PEGDA hydrogels have consistent trends, suggesting that the FFK/PEGDA hydrogels have the potential for long-term implantation. 31 3.5. Mechanical Properties.…”
Section: Hydrophilicitymentioning
confidence: 99%
“…The typical crystal structure characteristic absorption peaks of chitosan was observed at 2q ¼ 14.0 and 2q ¼ 20.8 . 22,23 Aer graing, the crystal structure changed to some extent, and the original characteristic absorption peak moved to about 2q ¼ 24.0 , and the intensity of the absorption peak was also relatively reduced. It is indicated that the introduction of AM and MAPTAC reduced the crystallinity of chitosan, which is mainly due to the introduction of side chains to increase the steric hindrance of CTS, thus weakening the hydrogen bond on the main chain of CTS, thereby damaging its crystal structure and making it amorphous.…”
Section: Resultsmentioning
confidence: 99%
“…Results showed excellent biodegradability and biocompatibility. Moreoever, its the best candidate for long-lasting local anesthetics development without causing significant toxicity [ 162 ].…”
Section: Biodegradable and Nondegradable Polymers For Wound Healingmentioning
confidence: 99%